Estado ambiental brasileiro : os dispositivos constitucionais que o fundamentam, algumas pré-compreensões necessárias e a atuação dos poderes públicos - Ribeiro, Lorena Costa (2014)
This research analyzed the possibility of characterize the current Brazilian State as an Environmental State and the consequences of this phenomenon. The concern with the environment preservation just began more strongly in the 70´s when the world started to realize the effects of inappropriate use of natural resources. It was recognized, since then, the existence of an environmental crisis that combined with the development phase that the world is, called by Ulrich Beck of risk society, promote the conditions to develop a new State model - the Environmental State - characterized by the insertion of the environmental concern among the governmental objectives. The national doctrine admits the adoption of the Environmental State according to 1988 Constitution because it is written in its text the obligation to protect the environment and as well as the recognition of the ecologically balanced environment as a fundamental right. To endorse this doctrinal position, the research investigated the presence of Environmental State characteristics in the 1988 constitutional text indicating the capable instruments to justify this statement. As the assumption of the existence of a Brazilian Environmental State was proved, the work studied two ways to contribute to the implementation of this new state model: the need for new pre-understandings from the Constitution interpreters as well as the requirement for new behaviors from the government. According to the Hans-George Gadamer philosophical rmeneutics, to understand something it is necessary a preunderstanding of the issue. Thus, to accomplish the Environmental State is necessary, initially, that the Constitution interpreter re-understands the ecological issues. In this sense, this work indicates four necessary pre-understandings to the implementation of the Brazilian Environmental State which are: the environmental crisis, the risk society and the creation of environmental problems, the need for a new relationship between man and nature, the concept of sustainable development and prohibition to retrogress in environmental subjects. In addition, it points out the ways to the Government achieve this new state model.